Sex steroid hormone levels associated with dopamine D2/3 receptor availability in people who smoke cigarettes - Zakiniaeiz, Yasmin; Gueorguieva, Ralitza; Peltier, MacKenzie R.; Verplaetse, Terril L.; Roberts, Walter; McKee, Sherry A.; Cosgrove, Kelly P. (Frontiers in Behavioral Neuroscience, 2023)
Introduction Sex differences exist in tobacco smoking. Women have greater difficulty quitting smoking than men. Tobacco smoking is driven by the reinforcing effects of nicotine, the primary addictive component in cigarettes. Nicotine binds to nicotinic acetylcholine receptors, facilitating dopamine release in striatal and cortical brain regions. Dysregulated dopamine D2/3 receptor signaling in the dorsolateral prefrontal cortex (dlPFC) is associated with cognitive deficits such as impairments in attention, learning, and inhibitory control that impede quit attempts. Sex steroid hormones, such as estradiol and progesterone, influence drug-taking behaviors, through dopaminergic actions, suggesting that their influence may explain sex differences in tobacco smoking. The goal of this study was to relate dlPFC dopamine metrics to sex steroid hormone levels in people who smoke and healthy controls. Methods Twenty-four (12 women) people who smoke cigarettes and 25 sex- and age-matched controls participated in two same-day [11C]FLB457 positron emission tomography scans, one before and one after amphetamine administration. D2R availability (BPND) at baseline and after amphetamine administration was calculated. On the same day, plasma samples were collected for the analysis of sex steroid hormone levels: estradiol, progesterone, and free testosterone. Results Women who smoke had trending lower levels of estradiol than their sex-matched counterparts. Men who smoke had higher levels of estradiol and trending higher levels of free testosterone than their sex-matched counterparts. Among women only, lower estradiol levels were significantly associated with lower pre-amphetamine dlPFC BPND. Discussion/conclusion This study demonstrated that lower estradiol levels are associated with lower dlPFC D2R availability in women which may underlie difficulty resisting smoking.